The Benefit Of Sponsorship Program : A Systematic Literature Review - Sukma, Fahrizal; Nafiah Ariyani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Sponsorship can be cost-effective in terms of reaching a particular audience. It allows access to specific audiences that otherwise might be difficult to achieve. All sectors of society can be targeted and gained through sponsorship. They are sports, the arts, education, community, and broadcast. Sponsorship can also achieve many different objectives, including increased awareness, image enhancement, and improved relationships with various publics. However, sponsorship also has disadvantages, so companies must prepare a risk mitigation plan. This research will reveal the benefits obtained by the company after implementing the sponsorship program. In detail, it will discuss which sectors are utilizing the sponsorship program, the purpose of conducting it, and the effects or benefits the company gets from implementing the sponsorship program. This study is based on a systematic literature review. The online research used the Google Scholar database by browsing titles, abstracts, and keywords to locate empirical research studies in peer-reviewed journals recently published in 2018-2022. They are 20 articles selected because of their rather relevance to the topic. The sports sector is the highest sector that utilizes sponsorship programs. Sponsorship of sports is not necessarily specific to sports; sponsorship has provided an opportunity for commercial advertising by corporations and businesses also represents the industrial component of the sport product and is manifested through commercial advertising of its industrial aspect. The majority of the researchers revealed how the effect of the sponsorship program. This is in line with the theory that one of the advantages of sponsorship programs is the results of sponsorship programs can be measured through surveys. Based on the analysis of selected articles, sponsorship programs provide many benefits for companies, such as increasing awareness and the credibility of companies and their products. Sponsorship programs provide shared value (engagement); for instance, in sports, this value is formed among sponsors, sports clubs, and athletes.